Ionic liquid-containing coordination polymer: solvent-free synthesis, incongruent melting, and glass formation. Issue 47 (23rd May 2022) - Mochida, Tomoyuki; Qiu, Yi; Funasako, Yusuke; Inokuchi, Makoto; Noguchi, Mariko; Fujimori, Hiroki; Furushima, Yoshitomo
Abstract : We prepared a 2-D coordination polymer that exhibits incongruent melting; the phase behavior was investigated in detail. Abstract : An ionic-liquid-containing 2D coordination polymer was synthesized via a solvent-free reaction. The material exhibited incongruent melting at 112 °C, forming a solid–liquid mixture; further heating to 240 °C led to complete melting. Upon cooling, the melt transformed into a solid–liquid mixture, from which the coordination polymer was gradually recovered at ambient temperature. Rapid cooling (>200 °C s −1 ) of the melt resulted in complete vitrification at −28 °C.